DESIGN OF JIG INSERT HOUSING TO PREVENT WORK ERRORS AT PT. AMBER KARYA - Dame Manalu (Universitas Riau Kepulauan, 2024)
Abstract: Growing industry in the world right now, then all the company continues to improve the quality of its products in the order to compete with other companies. One way the company is done by providing improved quality in the production process that aims to increase a better product without raising the cost of production. Improvement of product quality is done by creating a work tool that is easy to use and can reduce the number of errors on a production process to produce quality products that can compete in the global market.